Seroprevalence of Mycoplasma gallisepticum infection in backyard and commercial layer chickens in Bhola district, Bangladesh (Journal of Advanced Veterinary and Animal Research, 2014)
This study aimed to determine the seroprevalence of Mycoplasma gallisepticum (MG) infection in the chicken population of Bhola district, Bangladesh, during the period from April 2011 to March 2012. A total of 480 blood samples from chickens were collected from different upazilas (sub-districts) of Bhola district. The sampling considered the types of chicken (backyard and commercial layer), age groups (pullet, adult and old) and seasons (summer and winter). On the basis of the serum plate agglutination test, 55.83% (n=268/480) chickens were found positive for MG. The MG infection was higher (62.5%) in backyard chickens as compared to those being reared in commercial farming systems (53.61%). With respect to age groups, the prevalence was highest in pullets (60.63%) followed by adults (55.63%) and old chickens (51.25%). Moreover, chickens reared in winter showed higher prevalence of MG (60.42%) as compared to those reared in summer (51.25%). In conclusion, MG infection is prevalent in the chicken population of Bhola district, Bangladesh. Appropriate strategies should be taken for successful prevention and control of this disease in Bangladesh.DOI: http://dx.doi.org/10.5455/javar.v1i1p11-15 J. Adv. Vet. Anim. Res., 1(1): 11-15, March 2014